Understanding how behaviour therapists use autism spectrum disorder diagnostic information for intervention planning - Caven, Isabelle; Nguyen, Claire; Wiegelmann, Justine; Laframboise, Erica; Penner, Melanie (Frontiers in Psychiatry, 2023)
Understanding how behaviour therapists incorporate diagnostic assessments into their intervention planning can help to streamline assessment procedures and facilitate communication. The objectives are to identify what information from the diagnostic assessment is received by behaviour therapists and which assessment elements are most important and relevant for treatment planning. Behaviour therapists, identified through Ontario registries, were surveyed about their use of diagnostic information in treatment planning. Seventy-one behaviour therapists completed the survey (response rate = 35.5%). The diagnostic information most frequently received by respondents included brief (69%) and detailed (49.2%) physician/psychologist report, speech/language assessment report (52.1%) and individualized education plan (50.7%). Most respondents indicated that information from the physician/psychologist report is often out-dated (74.6% Agree/Strongly Agree). There was variable agreement that the information in the diagnostic package influences the type and quantity of treatment. These findings demonstrate that while diagnostic assessments received by behaviour therapists are important to their planning, other independently obtained sources of information, such as client interviews, are relatively more important to this process. The diagnostic assessment is one tool to inform treatment planning; however, up-to-date information about the child's needs is likely to be more informative.